Leituras críticas das narrativas hegemônicas sobre design: Glissant e teoria corpomídia no anúncio de designs por-vir - Medeiros, Patrícia Pimenta (2023)
This research aims to provide a critical reading of the design field, highlighting how hegemonic bases define and limit what is design. Design understood in a broad sense, because this discussion is not based on a supposed separation between theory and practice. Based on the theoretical supports of Édouard Glissant, with his Poetics of Relation (2005, 2014, 2021), and Katz and Greiner with the Bodymedia Theory (2001, 2006, 2008), the investigation not only proposes the critical analysis of the object in question, design, but suggests reading as an action. It pursues, thus, an orientation to the multiplicity of knowledges, which announce the possible designs to-come. The exposition of Glissant's thought supports both the counterpoint to the dominant discourses that continue to permeate relationships today and the importance of creating new narratives that foster diversity in the world. The Bodymedia Theory, on the other hand, supports the understanding of design not as a discipline that produces knowledge or isolated products, but as a communicational process that contaminates ways of life. The format of the dissertation, in conversation with Glissantian Errantry, abandons the usual script of chapters and proposes, through the construction of narratives supported by a bibliographical review, a re-reading of the foundations that sediment the discourses of design. These narratives represent discontinuous extensions, with no intention of reducing the object to the presented readings presented and aim to demonstrate how these power relations permeate such discourses, a question that presents itself as a research problem. To this end, these narratives explore the institutionalization of design in Brazil, the problematic of the history of design, the principles that underlie the elaboration of design methods, such as design thinking, as well as approaching design as bodymedia and presenting the motivations of the researcher, who has a long-standing relationship with the subject